Particle number size distribution and new particle formation under the influence of biomass burning at a high altitude background site at Mt. Yulong (3410 m), China - Shang, D. J.; Hu, M.; Zheng, J.; Qin, Y. H.; Du, Z. F.; Li, M. R.; Fang, J. Y.; Peng, J. F.; Y.S. Wu; Lu, S. H.; Guo, S. (Atmospheric Chemistry and Physics, 2018)
Biomass burning (BB) activities have a great impact on the particle number size distribution (PNSD) in the upper troposphere of the Tibetan Plateau, which could affect regional and global climate. An intensive campaign focused on the measurement of the PNSD, gaseous pollutants, and meteorological parameters was conducted at Mt. Yulong, a high-altitude site (3410ma.s.l.) on the southeastern Tibetan Plateau during the pre-monsoon season (22 March to 15 April). During this period, intensive BB activities in southern Asia were detected by fire maps. The long-range transport of BB pollutants can increase the accumulation mode particles in the background atmosphere at Mt. Yulong. As a consequence, the cloud condensation nuclei (CCN) concentration was found to be 2-8 times higher during BB periods than during clean periods. Apart from BB, variations of the planet boundary layer (PBL) and new particle formation (NPF) were other factors that influenced the PNSD. However, only three NPF events (with a frequency of 14 %) were observed at Mt. Yulong. The occurrence of NPF events during clean episodes corresponded to an elevated PBL or transported BB pollutants. Due to the lack of condensable vapors including sulfuric acid and organic compounds, the newly formed particles were not able to grow to CCN size. Our study emphasizes the influences of BB on the aerosol and CCN concentration in the atmosphere of the Tibetan Plateau. These results also have the potential to improve our understanding of the variation of the particle concentration in the upper troposphere, and provide information for regional and global climate models.
Keywords: anthropogenic aerosol; atmospheric brown clouds; chemical-composition; formation events; free troposphere; long-term; m a.s.l.; source apportionment; sulfuric-acid; tibetan plateau concentrations